(untitled) (Fiep Bulletin - online, 2012)
Introduction: Leprosy is an infectious disease caused by Mycobacterium leprae, which mainly affects the peripheral nerves and can cause absent or decreased sensitivity especially of the feet and hands. In individuals with neurological and systemic change is no correlation between plantar sensitivity and balance disorders as well as the distribution of pedal pressure, as is the case of individuals with leprosy. Objective: To analyze the baropodometry pedal pressure in patients suffering from leprosy treated at the Physical Rehabilitation Centre of the State University of West Paraná (Unioeste), Cascavel campus. Methods: 20 patients suffering from leprosy were assessed using an electronic baropodometric PRO Foot Work (Arkipelag), the platform is calibrated with information on the individual body mass. Each subject was evaluated in the standing position on the platform with your feet shoulder width apart, arms at your sides and bare feet. Results: The average load baropodometry revealed plantar forefoot was 51.3 ± 8% of the hindfoot of 48.8 ± 8%. In the left foot was 49.2 ± 4% and the right foot was 50.7 ± 4%. Comparing the anterior and posterior portions of the foot, there was more pressure on the forefoot (25.7 ± 2% pressure). Comparing the pressures of the forefoot, there was greater pressure on the right forefoot (27.0 ± 7%) in the peak plantar pressure, 60% (12 patients) of the sample had a greater pressure on the forefoot (1.24 kgf / cm2), and the majority (8 patients) had an average of 1.2 Kgf/cm2 the right forefoot, and the remainder received an average of 1.3 Kgf/cm2 in the anterior portion of the left foot. Eight participants had a greater pressure on the hindfoot, and 4 with an average of 1.4 Kgf/cm2 on the left and four with an average of 1.2 Kgf/cm2 right hindfoot. In the right and left foot peak pressure was 0.3 kgf/cm2. Conclusions: We conclude from this study that the sample has higher values of plantar pressure in the anterior portion of the foot, the latter having a predisposition for plantar ulcer formation in this region, since an abnormal distribution of load on the plantar surface leads to trauma to the area of higher pressure.